2012
DOI: 10.1016/j.yrtph.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a total allowable concentration of o-toluidine in drinking water incorporating early lifestage exposure and susceptibility

Abstract: o-Toluidine is a monocyclic aromatic amine present in the formulation of some materials that contact drinking water. NSF/ANSI 61 Annex A (2011) and US EPA (2005a) risk assessment guidelines were used to determine an acceptable drinking water level. Occupational exposure to o-toluidine is associated with an increased risk of bladder cancer but human disease rates could not be used to establish risk values due to inadequate exposure data and coexposures in the epidemiology cohorts. Chronic dietary exposure to o-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 71 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the mutagenic activity of OTD is controversial. In several studies, including ours, OTD did not exhibit mutagenicity in the Ames salmonella assay with or without metabolic activation systems [3,28,29]. However, Beyerbach et al reported that the 2 ′ -deoxyguanosine-8-yl-OTD (2-methylaniline) adduct could be chemically synthesized [7].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the mutagenic activity of OTD is controversial. In several studies, including ours, OTD did not exhibit mutagenicity in the Ames salmonella assay with or without metabolic activation systems [3,28,29]. However, Beyerbach et al reported that the 2 ′ -deoxyguanosine-8-yl-OTD (2-methylaniline) adduct could be chemically synthesized [7].…”
Section: Discussionmentioning
confidence: 71%
“…Thus, the possible mechanisms of OTD genotoxicity are shown in Figure 6. The p-aminophenol metabolites of OTD, N-acethyl-4-amino-m-cresol, are thought to form protein adducts in urinary epithelial cells [29], which might stimulate immune cells and possibly induce inflammation along with ROS production via NADPH oxidase. This hypothesis was tested by conducting an animal experiment, which confirmed the effect of the NADPH oxidase inhibitor, apocynin, on urinary epithelial hyperplasia in rats induced by OTD (Figure 5).…”
Section: Discussionmentioning
confidence: 99%